Actividades lúdicas tradicionales y el desarrollo de la motricidad gruesa en los niños del Centro de Desarrollo Infantil “Galapaguitos”, Riobamba. - Fanny Leonor Miranda Guevara (2020)
The goal of this investigation is to show that the “Jugando en el Galapaguitos” traditional playful activities guidebook strengthens the development of gross motor skills in children at the “Galapaguitos” Child Development Center, Riobamba. A pre-experimental design was applied with a quantitative approach. There was a population of sixty-three children. The formula for the finite population suggested working with a sample population of fifty-four children. The investigation used the observation technique to collect information. The data collected to evaluate the development of the gross motor skills of each child was recorded in an observation sheet. The data were organized according to the qualitative scale (started, in process, acquired), and it was used before and after the application of the guidebook. The analysis of the data included tabulation, graphs, and interpretation of the data. The analysis of the data showed a hypothesis, and this was verified through the difference of proportions statistical test. The difference of proportions statistical test affirms that the percentage of children who showed gross motor development on the acquired scale was higher after the application of the “Jugando en el Galapaguitos” traditional playful activities guidebook. In conclusion, the guidebook helped to strengthen and increase the development of skills that children must control in their early childhood. These skills include the body exploration and gross motor skills.